Leder ökad medellängd på massaved till ökad prestation vid skotning i gallring? - Nordstrand, Johan; Sandberg, Carl Philip (SLU/School for Forest Management, 2018)
The purpose of this project was to determine whether the production of a forwarder is more effective when the wood is cut into pieces with an average length of 4,8 meters compared to 4,5 meters. Before the test was carried out, a harvester felled and cut the wood in a total of eighteen sample surfaces. Each of the samples surfaces had a volume of 8 m3fub felled wood. All the sample surfaces had the same topography with Norway spruce. The result of the study revealed that the forwarder was more effective in loading and unloading when the average length of the wood pieces was 4,8 meters. The average time it took for the forwarder to both load and unload was 15,17 minutes compared to 17,45 minutes.